PGF2α induces a pro-labour phenotypical switch in human myometrial cells that can be inhibited with PGF2α receptor antagonists - Hamshaw, Isabel; Straube, Anne; Stark, Richard; Baxter, Laura; Alam, Mohammad T.; Wever, Walter J.; Yin, Jun; Yue, Yong; Pinton, Philippe; Sen, Aritro; Ferguson, Gregory D.; Blanks, Andrew M. (Frontiers in Pharmacology, 2023)
Preterm birth is the leading cause of infant morbidity and mortality. There has been an interest in developing prostaglandin F2α (PGF2α) antagonists as a new treatment for preterm birth, although much of the rationale for their use is based on studies in rodents where PGF2α initiates labour by regressing the corpus luteum and reducing systemic progesterone concentrations. How PGF2α antagonism would act in humans who do not have a fall in systemic progesterone remains unclear. One possibility, in addition to an acute stimulation of contractions, is a direct alteration of the myometrial smooth muscle cell state towards a pro-labour phenotype. In this study, we developed an immortalised myometrial cell line, MYLA, derived from myometrial tissue obtained from a pregnant, non-labouring patient, as well as a novel class of PGF2α receptor (FP) antagonist. We verified the functionality of the cell line by stimulation with PGF2α, resulting in Gαq-specific coupling and Ca2+ release, which were inhibited by FP antagonism. Compared to four published FP receptor antagonists, the novel FP antagonist N582707 was the most potent compound [Fmax 7.67 ± 0.63 (IC50 21.26 nM), AUC 7.30 ± 0.32 (IC50 50.43 nM), and frequency of Ca2+ oscillations 7.66 ± 0.41 (IC50 22.15 nM)]. RNA-sequencing of the MYLA cell line at 1, 3, 6, 12, 24, and 48 h post PGF2α treatment revealed a transforming phenotype from a fibroblastic to smooth muscle mRNA profile. PGF2α treatment increased the expression of MYLK, CALD1, and CNN1 as well as the pro-labour genes OXTR, IL6, and IL11, which were inhibited by FP antagonism. Concomitant with the inhibition of a smooth muscle, pro-labour transition, FP antagonism increased the expression of the fibroblast marker genes DCN, FBLN1, and PDGFRA. Our findings suggest that in addition to the well-described acute contractile effect, PGF2α transforms myometrial smooth muscle cells from a myofibroblast to a smooth muscle, pro-labour–like state and that the novel compound N582707 has the potential for prophylactic use in preterm labour management beyond its use as an acute tocolytic drug.